2020
DOI: 10.18632/aging.102811
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in renal fibrosis

Abstract: Renal fibrosis is an inevitable consequence of parenchymal scarring and is the common final pathway that mediates almost all progressive renal diseases. Adiponectin, a hormone produced by adipose tissue, possesses potent anti-insulin, anti-inflammatory, and anti-fibrotic properties. Reportedly, adiponectin serves as an important messenger that facilitates complex interactions between adipose tissue and other metabolically related organs. In recent years, a growing body of evidence supports adiponectin involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Activation of the AMPK pathway after the binding of APN to AdipoR1 inhibits its downstream pathway, significantly resisting stress, inhibiting protein synthesis, and preventing fibrosis [14,15]. Therefore, the AdipoR1-AMPK pathway plays an important role in maintaining the normal physiological homeostasis of the kidney [3]. The study confirmed that the APN decreased in patients with coronary artery disease and metabolic syndrome [16,17]; still, the APN was at a high level in different stages of CKD [18,19,20].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Activation of the AMPK pathway after the binding of APN to AdipoR1 inhibits its downstream pathway, significantly resisting stress, inhibiting protein synthesis, and preventing fibrosis [14,15]. Therefore, the AdipoR1-AMPK pathway plays an important role in maintaining the normal physiological homeostasis of the kidney [3]. The study confirmed that the APN decreased in patients with coronary artery disease and metabolic syndrome [16,17]; still, the APN was at a high level in different stages of CKD [18,19,20].…”
Section: Discussionmentioning
confidence: 60%
“…APN has the effects of insulinsensitizing, anti-inflammation, and anti-atherosclerosis. Some scholars have found that the AdipoR1-AMP-activated protein kinase (AMPK) pathway can maintain the normal physiological homeostasis of the kidney [3]. Serum uric acid (UA) is an independent predictor of the development, progress, and prognosis of primary nephrotic syndrome (PNS) [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…CKD is becoming a public health problem, which affects more than 10% of the global population (Huang et al., 2021 ). Although initiated by various aetiologies, renal fibrosis is a final common pathological change in all types of CKD (Gewin, 2018 ; Jing et al., 2020 ). Although therapies such as dialysis and transplantation can ameliorate or delay the progression of renal fibrosis, there are currently no curative strategies (Nastase et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high morbidity and mortality of CKD brings a heavy burden to medical care and economy development ( Jha et al, 2012 ; Nastase et al, 2018 ). Notably, renal fibrosis is the key pathological feature in the progression of CKD into ESRD ( Gewin, 2018 ; Jing et al, 2020 ). To clarify the underlying mechanisms of renal fibrosis is valuable to retard the development of CKD and lessens the medical and financial burden.…”
Section: Introductionmentioning
confidence: 99%